Electron microscopy of the plexiform lesion. Issue 2 (April 1979) - Smith, P; Heath, D
Abstract : Pulmonary arteries from a case of plexogenic pulmonary arteriopathy were studied with the electron microscope. Many muscular pulmonary arteries showed intimal fibrosis of concentric or "onion-skin" type. The cells embedded within this fibrosis resembled smooth muscle but since they also possessed some features of fibroblasts we refer to them as myofibroblasts. Myofibroblasts also occurred in plexiform lesions together with fibroblasts and "fibrillary cells". These fibrillary cells contained numerous, prominent filaments with a random orientation. They lined the vascular channels of the plexiform lesions as well as being present within the stroma. They appeared to phagocytose fibrin and then to organise the plexiform lesion into a fibrous scar. Fibrillary cells closely resemble vasoformative reserve cells and the cells of the cardiac myxoma and so-called "papillary tumour" of heart valves. They may, therefore, be primitive multipotential cells found throughout the entire cardiovascular system.